Effects of antenna directivity on RF ranging when using space diversity techniques. (February 2017) - Pasku, Valter; Fravolini, Mario Luca; Moschitta, Antonio
Highlights: A multipath mitigation for a RSSI based ranging system based on antenna diversity is extended. Effect of antennas' directivity and rotations is investigated and discussed. Sensitivity of the mitigation techniques to RSSI inaccuracy is investigated. Abstract: In this paper, a ranging technique based on narrowband transmissions in the 2.4 GHz ISM band is discussed. Multipath mitigation techniques based on Multiple Input Multiple Output (MIMO) philosophy are considered, discussing the effect of antenna rotations on the achievable performance under Line of Sight conditions, and the effect of RSSI measurement uncertainty on the effectiveness of the mitigation techniques. Simulation and experimental results show that the proposed approach can effectively improve the ranging accuracy.